AB1003 Validation of Lay Descriptions of Levels of Severity of Knee and Hip OA in The Khoala Cohort Study. (15th July 2016) - Guillemin, F.; Cross, M.; Ngueyon Sime, W.; March, L.
Abstract : Background: Estimating the proportion of the population with severe OA is of use in health service planning. To calculate the proportion of the population with mild, moderate or severe OA, the Global Burden of Disease 2010 Study (GBD2010) used published WOMAC scores. From this, the proportion of the population in high income countries with mild OA was estimated as 71%, moderate 27% and severe 2%. Lay descriptions of levels of severity of OA were developed for GBD2010. If these are accurate measures of disease severity, these descriptions would be useful additions to population-based health questionnaires or brief assessments in clinical practice. Objectives: To validate lay descriptions of mild, moderate and severe OA and determine the proportion of a cohort within each category. Methods: Descriptions were presented to the KHOALA cohort comprising 878 OA knee and hip prevalent cases recruited as a representative sample of French patients with clinical and radiographic OA. Participants were asked to indicate which description they felt best described their condition. An additional level of "No pain or disability" was added for this cohort. Mild OA was described as "Has pain in the leg, which causes some difficulty running, walking long distances, and getting up and down" Moderate OA: "Has moderate pain in the leg, which makes the person limp, and causes some difficulty walking, standing, lifting and carrying heavy things, getting up and down and sleeping" Severe OA: "Has severe pain in the leg, which makes the person limp and causes a lot of difficulty walking, standing, lifting and carrying heavy things, getting up and down, and sleeping" Participants also completed WOMAC, EQ5D, EUROQOL VAS and walking times. Results: Currently, 307 participants have completed the questionnaire with results shown below. There was a significant trend for the WOMAC, EQ5D, EUROQOL and Maximal walking time to decline as self-reported level of severity moved from none through mild and moderate to severe. The lay descriptions show significant convergent and divergent validity with the standardized measures used. Conclusions: These preliminary results suggest that the lay descriptions are understandable by participants in this cohort. Those who rated their condition as consistent with the severe description also scored worse on the measures of pain and function. 14% classified themselves as having severe OA, in contrast to GBD2010, where only 2% were classified as having severe OA. The burden of OA may in fact be greater than reported in GBD2010 as the proportion of the population living with more severe disease may have been underestimated. Further assessment is being undertaken with a larger sample of the KHOALA cohort. These lay descriptions may be useful as a brief starting point for discussions in clinical care, or a contribution to the assessment of severity of OA. Disclosure of Interest: None declared